2021
DOI: 10.1097/mat.0000000000001562
|View full text |Cite
|
Sign up to set email alerts
|

Applications and Outcomes of Extracorporeal Life Support Use in Adult Liver Transplantation: A Case Series and Review of Literature

Abstract: The use of extracorporeal life support (ECLS) is increasingly reported in adult liver transplantation (LT). However, neither the role of ECLS in the perioperative setting for LT nor its outcomes has been well defined. We performed a retrospective chart review of all adult LT patients at our institution who received ECLS from 2004 to 2021. We also conducted a comprehensive literature search for adult LT cases that involved perioperative ECLS for respiratory or cardiac failure. Over the study period, 11 LT patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Four of these patients could not be weaned from ECMO and expired. 7 These results suggest that—in a scenario in which the donor organ has not yet been implanted—reallocation of the organ should be strongly considered and VA-ECMO during the transplant should be reserved only for potentially reversible conditions occurring in the neohepatic or postoperative phase of LT with a functioning graft.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four of these patients could not be weaned from ECMO and expired. 7 These results suggest that—in a scenario in which the donor organ has not yet been implanted—reallocation of the organ should be strongly considered and VA-ECMO during the transplant should be reserved only for potentially reversible conditions occurring in the neohepatic or postoperative phase of LT with a functioning graft.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Park et al . 7 report the use of VA-ECMO during LT in nine patients to manage acute cardiac failure caused by intracardiac thrombus, massive pulmonary embolism, stress-induced cardiomyopathy, or isolated right-ventricle failure. Five patients (55.6%) had a cardiac arrest and were placed on VA-ECMO under extracorporeal life-support.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that prompt ECMO initiation may benefit graft survival. 4,13 More research is needed to determine the optimal timing of ECMO initiation in children after liver transplant. The elevated mortality in the ECPR group in our cohort might be attributed to the fact that the patients undergoing ECPR might constitute a specific group of children.…”
Section: Discussionmentioning
confidence: 99%
“…Given the increased prevalence of severe cardiovascular comorbidities and increased incidence of higher-risk LT recipients, experience with extracorporeal life support (ECLS), including extracorporeal membrane oxygenation (ECMO), is increasingly reported in adult LT. Rark and associates conducted a comprehensive literature search for adult LT cases that involved perioperative ECLS for respiratory or cardiac failure. 67 They identified 35 cases of respiratory failure in LT patients requiring perioperative ECLS. Applications included a preoperative bridge to LT (n = 6) and postoperative rescue (n = 29), for which overall survival was 44%.…”
Section: Liver Transplantationmentioning
confidence: 99%